2021
DOI: 10.3389/fpubh.2021.676000
|View full text |Cite
|
Sign up to set email alerts
|

Refugee Mental Health, Global Health Policy, and the Syrian Crisis

Abstract: The most recent global refugee figures are staggering, with over 82.4 million people forcibly displaced and 26.4 million registered refugees. The ongoing conflict in Syria is a major contributor. After a decade of violence and destabilization, over 13.4 million Syrians have been displaced, including 6.7 million internally displaced persons and 6.7 million refugees registered in other countries. Beyond the immediate political and economic challenges, an essential component of any response to this humanitarian c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 189 publications
(228 reference statements)
0
9
0
Order By: Relevance
“…7 Compared with Syrians, Afghan refugees are relatively understudied. The massive influx of Syrian refugees to neighbouring countries has attracted significant scholarly attention to their mental health and their displacement conditions, 8,9 but there has been less of such research on Afghan refugees in the Middle East and Türkiye. 10 Many Syrians and Afghans have experienced severe potentially traumatic events such as witnessing atrocities, prolonged deprivation and the loss of loved ones either in their home country or en route to destination countries, all of which negatively affect their mental health and well-being and may undermine their adaptive abilities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7 Compared with Syrians, Afghan refugees are relatively understudied. The massive influx of Syrian refugees to neighbouring countries has attracted significant scholarly attention to their mental health and their displacement conditions, 8,9 but there has been less of such research on Afghan refugees in the Middle East and Türkiye. 10 Many Syrians and Afghans have experienced severe potentially traumatic events such as witnessing atrocities, prolonged deprivation and the loss of loved ones either in their home country or en route to destination countries, all of which negatively affect their mental health and well-being and may undermine their adaptive abilities.…”
mentioning
confidence: 99%
“… 7 Compared with Syrians, Afghan refugees are relatively understudied. The massive influx of Syrian refugees to neighbouring countries has attracted significant scholarly attention to their mental health and their displacement conditions, 8 , 9 but there has been less of such research on Afghan refugees in the Middle East and Türkiye. 10 …”
mentioning
confidence: 99%
“…CAU refers to all (mental) health services available to refugees in the setting where the pragmatic trial is conducted 36. Although study sites differ with regard to the availability of services, barriers to accessing care have been identified across host countries 13 15 37…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies have indicated that experiencing additional trauma in the host country is a critical post-migration factor in worsening trauma-related symptoms in refugee populations [ 38 , 39 ]. Among Syrian refugees, factors such as racial discrimination, integration difficulties, language barriers, loss of social relationships, culture shock, fear of deportation, long stays in refugee camps, and high living costs contributed to the burden of psychological disorders [ 4 , 5 , 17 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%